Cross-sectional associations of pulmonary function with systemic inflammation and oxidative stress in individuals with chronic spinal cord injury. (3rd May 2016) - Hart, Jaime E.; Morse, Leslie; Tun, Carlos G.; Brown, Robert; Garshick, Eric
Abstract : Context/Objective: Systemic inflammation, and to a lesser extent oxidative stress, have been associated with reduced pulmonary function. Our objective was to evaluate the associations between biomarkers of inflammation (C-reactive protein (CRP), interleukin-6 (IL-6)) and novel makers of global oxidative stress (fluorescent oxidation products (FLOx)) with spirometric and lung volume measures in individuals with chronic spinal cord injury (SCI). Design: Cross-sectional study. Setting: Veterans Affairs Medical Center. Participants: One-hundred thirty-seven men with chronic SCI participating in an epidemiologic study. Methods: Participants provided a blood sample, completed health questionnaires, and underwent pulmonary function testing, including helium dilution measurement of functional residual capacity (FRC). General linear models were used to model associations between increasing quartiles of inflammation or oxidative stress with each outcome measure, after adjustment for a number of potential confounders. Outcome Measures: Percent-predicted forced vital capacity in one second (FEV1 ), percent-predicted forced vital capacity (FVC), FEV1 /FVC, percent-predicted residual volume (RV), percent-predicted FRC, and percent-predicted total lung capacity (TLC). Results: After adjustment for a number of confounders, participants with higher levels of CRP and IL-6 had lower percent-predicted FEV1 and FVC measurements. There were no clear patterns of association with any of the oxidative stress biomarkers or other outcome measures. Conclusion: Increased systemic inflammation was associated with reductions in FEV1 and FVC independent of a number of covariates. Although the mechanism is uncertain, these results suggest that reductions in pulmonary function in SCI are associated with systemic inflammation.